2022
DOI: 10.3390/v14091912
|View full text |Cite
|
Sign up to set email alerts
|

The African Swine Fever Isolate ASFV-Kenya-IX-1033 Is Highly Virulent and Stable after Propagation in the Wild Boar Cell Line WSL

Abstract: We describe the characterization of an African swine fever genotype IX virus (ASFV-Kenya-IX-1033), which was isolated from a domestic pig in western Kenya during a reported outbreak. This includes the efficiency of virus replication and in vivo virulence, together with genome stability and virulence, following passage in blood macrophages and in a wild boar lung cell line (WSL). The ASFV-Kenya-IX-1033 stock retained its ability to replicate in primary macrophages and retained virulence in vivo, following more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…In our study, all pigs survived to day 23 days post ASFV infection, then all the animals were euthanised. The animals in this study displayed clinical signs that are similar to the low dose group (1 HAD 50 ) reported by Hemmink, clinical signs were much milder than the titer of 10 2 HAD 50 ( Hemmink et al , 2022 ). ASFV is known to infect pigs of all ages.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, all pigs survived to day 23 days post ASFV infection, then all the animals were euthanised. The animals in this study displayed clinical signs that are similar to the low dose group (1 HAD 50 ) reported by Hemmink, clinical signs were much milder than the titer of 10 2 HAD 50 ( Hemmink et al , 2022 ). ASFV is known to infect pigs of all ages.…”
Section: Discussionsupporting
confidence: 86%
“…The essential roles of MGF proteins in in vivo infections, virulence and immune escape have been demonstrated repeatedly [ 47 , 48 , 49 , 50 ]. It should be noted that strains BA71V and ASFV-Kenya-IX-1033 contain deletions of some genes of MGF110, MGF360 and MGF505, in contrast to ASFV strains K49, Georgia 2010 and Malawi Lil-20/1 [ 29 , 37 , 51 , 52 , 53 , 54 ]. This issue requires a more detailed study in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The virus was adapted to efficient growth in cell culture through 21 serial passages on WSL cells. The genotype IX isolate ASFV Kenya 1033 55 , 75 was kindly provided by Richard Bishop (International Livestock Research Institute, Nairobi, Kenya). The mutant ASFV Kenya 1033 ΔCD2v dsRed containing a reporter gene expression cassette at the deleted CD2v (EP402R) gene locus 55 , 56 was kindly provided by Günther M. Keil (FLI).…”
Section: Methodsmentioning
confidence: 99%